IMPACT OF INTERNET OF THINGS ON SUSTAINABLE SUPPLY CHAIN PERFORMANCE: THE EMPIRICAL PARALLEL MEDIATION MODELS - Fahad Saddique; Khalil Nasir Khan; Sher Zaman Joyia; Affia Jabeen (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
Manufacturing companies in this era struggle to develop an integration mechanism for sustainability in the Pakistan context. Manufacturing firm performance highly depends upon integrating a digital supply chain to gain competitive advantages. Therefore, this present study shows the influence of the internet of things on sustainable supply chain performance in manufacturing organizations in Pakistan. Furthermore, The mediating roles of digital supply chain integration and competitive advantage between sustainable performance and internet of things. This study sample data is based on 369 respondents from manufacturing organizations in Pakistan. The study results showed that the Internet positively influences sustainable performance in manufacturing organizations in Pakistan. Furthermore, there are partial mediating roles of median digital integration and competitive advantage between the internet of things and sustainability. This study helps regulators and policymakers use the latest technologies for business growth.